Dekontruksi Pasal 25 Kompilasi Hukum Islam Tentang Kesaksian Perempuan dalam Perkawinan - Abdul Malik Syafe’i (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
One of the issues still being debated today is the women testimony, specially in marriage. Previous study found that in the KHI women are not be able to be a witness. As stated in article 25 of KHI “That may be designated as a witness in the marriage contract is a Islam male, fair, understanding, mature, uninterupted memory and is not deaf or hard of hearing”. By using the normative legal research methode (juridical) with statute approach and using content theory as legal materials analysis techniques. This study found that the KHI has used by the headman as referenced in determining marriage witness, in that found there were many drawbacks, in addition it was look like a breakdown of The Marriage Law No 1 of 1974, as well as the basics of the article is almost entirely abstracted from Fiqh Syafiiyah books. In fact, the Qur'an and the hadith are not forbid women to be witness. Likewise in the Constitution, women have the equality before the law. For that we need the deconstruction of KHI Article 25 by providing opportunities for women to witness the marriage. Considering that The KHI is part of the rules of law, accordingly for reform it should be made by the president himself as an executive or judicial review to the Constitutional Court.